Gender diversity and dividend payout - Kok, Yong Le (2019)
This paper is an effort to reveal the empirical insights relating to gender diversity and firm-specific characteristics on dividend payout with reference to 25 public listed companies on Malaysia’s FBM KLCI over the period of 2010 to 2017 (8 years). In light of prior literature, key explanatory variables were identified to disclose their relationship and effect on determination of dividend payout. These variables are CEO gender, female directors on board, profitability, financial leverage, cash flows, firm size and growth opportunities. Data were obtained from DataStream and annual reports of the sampled companies. In analysing the data, the study used Fixed Effects Model (FEM) and was based on three dividend theories: signalling theory, agency theory and pecking order theory. This study evidence that dividend payout by entire sampled companies has a positive significant relationship to female directors on board, profitability, cash flows, firm size and a negative significant relationship to CEO gender and financial leverage. The second objective of this study is to ascertain to what extent the difference between determinants affecting dividend payout of banks and non-bank companies. The dividend payout of banks and non-bank companies have a positive significant relationship to firm size and negative significant relationship to financial leverage. Contrariwise, empirical results for banks show only cash flows have positive significant effect on dividend payout whereas female directors on board and profitability are positive significant to explain dividend payout of non-bank companies.